Investigation of coenzyme Q10 levels and predisposing factors in patients with striae gravidarum - Yüksel, Mavişe; Lebriz Aktün, Hale; Balevi, Ali; Çakıcı, Çağrı; Ülfer, Gözde (Wiley, 2020)
Background: Striae gravidarum (SG) can cause pregnant women severe psychological stress. Objective: This study aimed to compare primigravidas with and without SG concerning fasting blood coenzyme Q10 (CoQ10), age, skin type, family history, gestational weight gain, pre- and post-pregnancy BMI, daily water consumption during pregnancy, gender and weight of baby, and the educational level. Methods: The study included 79 primigravidas in the gestational week of 36 or above. The patients were divided into two groups based on the presence of SG. The fasting blood CoQ10 levels and other associated parameters were compared between the groups. Results: Of the 79 primigravidas, 35 (44.3%) had SG. There was no statistically significant relationship between striae and CoQ10 (P = 0.144 and P = 0.189, respectively). Predisposing factors for striae were young pregnancy, light skin color, family history, high pre- and post-pregnancy BMI, increased gestational weight gain, and increased newborn weight. There was no significant relationship between striae development and educational level or water consumption during pregnancy. Conclusion: This is the first study to show that CoQ10 did not significantly differ between women with and without SG. Further studies with a larger case series are needed to elucidate predisposing factors for striae and involvement of CoQ10 in this condition.
Keywords: Coenzyme Q10; Collagen; Elastin; Striae Gravidarum